A Regularized Algorithm for the Proximal Split Feasibility Problem. (1st July 2014) - Yao, Zhangsong; Cho, Sun Young; Kang, Shin Min; Zhu, Li-Jun
Abstract : The proximal split feasibility problem has been studied. A regularized method has been presented for solving the proximal split feasibility problem. Strong convergence theorem is given.